The impact of CEO gender on earnings management: evidence from China - Sun, Jingyi (2022)
The impact of CEO gender on earnings management is examined using data from Chinese publicly traded companies from 2015 to 2020. According to the findings of this research, female CEOs have no significant impact on accrual-based earnings management, but are significantly negatively correlated with real activity-based earnings management. In general, disparities in CEO gender have an impact on earnings management as gender-related personal characteristics like risk appetite, morality, and self-confidence can influence female and male executives' decision-making tendencies.